THE IMPORTANCE OF AGROECOLOGY WITH FAMILY FARMING - Francisco de Moura Junior, José; de Souza Possimoser, Deivison (Journal of Interdisciplinary Debates, 2023)
One of the major concerns of nations in recent times is the food sovereignty of the world population, linked to all this comes the issue of sustainability, since the larger the population, the greater the demand for food, to produce a lot of food an even larger portion of land will be needed and, the soil has been becoming weak lately due to excessive degradation and use without due care, Agroecology appears as an alternative to producing food without damaging the soil so much, as it is an aspect focused on sustainability, that is, it will produce without harming the environment and much less the soil, agroecology kind of imitates the way plants interact in consortia, it is clear that agroecology at the moment cannot be implemented on a large scale, but in family farming, yes, it is possible, since the family farmer does not produce on a large scale, this family production is restricted to small family groups as the name suggests, “Family Farming”. The green revolution had a beautiful objective, but in the end it failed drastically, its objective was to end world hunger and in the end, it only served to fulfill political and economic goals.